(untitled) (Research, Society and Development, 2022)
The clinical pharmacy is concerned with solving and avoiding drug-related problems. The clinical pharmacist works focused on the pharmacotherapy and clinical condition of the assisted person; its work is also carried out in multidisciplinary cooperation, embracing the integrality of the SUS. This article focuses on the report of the experiences lived by a clinical pharmacist in the surgical clinic of a teaching hospital from September 2020 to February 2021, in times of COVID-19. As for the method, it is an experience report of the activities developed by the professional and supervised by the preceptor clinical pharmacist. The discussions were guided based on what was experienced in the clinic, being arranged in guiding axes of discussion, addressing topics relevant to the professional performance of the pharmacist. This professional proved to be crucial in times of the COVID-19 pandemic, in education, medication review, monitoring of adverse reactions and laboratory tests, and in providing medication-related guidance and recommendations. Therefore, it was possible to highlight the importance of the clinical pharmacist in the competence of integrality, this has relevance in public health, being crucial in the times of the COVID-19 pandemic, based on health education and the rational use of medicines.